Application of Cupping Therapy with Ginger Aromatherapy on Reducing Cholesterol Level among Patients with Hypercholesterolemia - Mayu Sanlia Samadani; Mardiyono Mardiyono; M. Choiroel Anwar (International Journal of Nursing and Health Services (IJNHS), 2021)
Hypercholesterolemia is a significant risk factor for cardiovascular disease. Cholesterol can interfere with and change blood vessels' structure, resulting in impaired endothelial function causing lesions, plaques, occlusion, and embolism. Cupping therapy with ginger aromatherapy is one alternative treatment for hypercholesterolemia. It improved lipid profile levels. The study aimed to examine the effect of cupping therapy with ginger aromatherapy on reducing the lipid profile levels among hypercholesterolemia patients. This true experimental study design, pre-test, and post-test with non-equivalent control group design was applied in this study. Thirty samples were selected into the experimental group and the control group. The intervention group received the cupping therapy with ginger aromatherapy, while the control group only received the10 gr simvastatin drug per day. The lipid profile levels were measured on day 1 and day 21. The result showed a significant difference between the experimental group and the control group with a p-value<0.05. In conclusion, it was found that cupping therapy with ginger aromatherapy for 21 days was effective in reducing lipid profile levels among hypercholesterolemia patients. Further researchers are expected to develop research on cupping therapy's benefits with ginger aromatherapy to reduce lipid profiles or other pathological conditions